Heinrich Heine : writing the revolution - Prochnik, George (New Haven : Yale University Press, 2020)
A thematically rich, provocative, and lyrical study of one of Germany's most important, world-famous, and imaginative writers.
Frontmatter -- Contents -- Heinrich Heine -- References and acknowledgments -- Index
Inlcudes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, viewed on December 04, 2020).
JSTOR
Keywords: Heine, Heinrich, -- 1797-1856.; Heine, Heinrich, -- 1797-1856 -- Criticism and interpretation; Heine, Heinrich, -- 1797-1856; Authors, German -- 19th century -- Biography; Écrivains allemands -- 19e siècle -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Authors, German; 1800-1899; Biography; Biographies; Criticism, interpretation, etc; Biographies; Biographies